A Theoretical Model to Discuss Tax Avoidance Based gn Game Theory - Antônio Paulo Machado Gomes; Jacqueline Veneroso Alves da Cunha; José Roberto de Souza Francisco; Fabiano Teodoro de Rezende Lara (BBR: Brazilian Business Review)
A consolidated research line in Brazil identified the proxies for determining the tax aggressiveness of companies listed on the B3 stock exchange. However, none of these studies identified the instrument used by Brazilian companies to carry out tax aggressiveness. Thus, our research seeks to fill this gap by demonstrating that fiscal aggressiveness results from the Brazilian tax complexity, that providing prerogatives to avoid or delay tax payments. Besides, this study is the first accounting study to demonstrate that special installments reduce the actual value of taxes owed by taxpayers, encouraging them to be tax aggressive. Through the foundations of Game Theory, this research demonstrates the cost-benefit of tax aggressiveness in maximizing the profit of tax avoidance. We examined the best strategic decisions in the tax avoidance game concerning the tax complexity and special installments experienced in Brazil. In this game, the only NASH equilibrium is tax avoidance since it is the only option with a chance of remuneration. Therefore, this research contributes to understanding business behavior concerning the Brazilian tax system and provides subsidies to encourage reform of the current tax complexity.